Novel electrode materials for electrochemical capacitors : Part II. Material characterization of sol-gel-derived and electrodeposited manganese dioxide thin films - Pang, Suh Cem; Anderson, Marc A. (Cambridge University Press, 2000)
Material characterization of sol-gel-derived and electrodeposited MnO2 thin films showed that their microstructures are highly porous in nature. While sol-gel-derived films are nanoparticulate, electrodeposited films showed macropores of random and irregular platelike structures, comprising much denser surface layers and highly porous underlying layers. On the basis of calculated and theoretical density values of 1 and 4.99 g/cm3 , respectively, the porosity of sol-gel-derived MnO2 films was determined to be as high as 80%, which is substantially higher than electrodeposited films at 67%. Apart from their higher specific capacitance, sol-gel-derived MnO2 films appeared to exhibit higher cycling stability and reversibility than electrodeposited MnO2 films. In the case of sol-gel films, thinner films appeared to exhibit higher cycling stability than thicker films. There was less alteration in surface morphology and microstructure, and the rate of loss in charge-storage capacity upon voltammetric cycling was not as significant for sol-gel MnO2 thin films.